Usefulness of endoscopic ultrasound-guided fine-needle biopsy for the diagnosis of autoimmune pancreatitis using a 22-gauge Franseen needle: a prospective multicenter study - Ishikawa, Takuya; Kawashima, Hiroki; Ohno, Eizaburo; Suhara, Hiroki; Hayashi, Daijuro; Hiramatsu, Takeshi; Matsubara, Hiroshi; Suzuki, Takahisa; Kuwahara, Takamichi; Ishikawa, Eri; Shimoyama, Yoshie; Kinoshita, Fumie; Hirooka, Yoshiki; Fujishiro, Mitsuhiro (Endoscopy, 2020)
Background Detailed histological evaluation is important in the diagnosis of autoimmune pancreatitis (AIP). However, it remains challenging to obtain adequate tissue from the pancreas. Recently, several reports have suggested the usefulness of endoscopic ultrasound-guided fine-needle biopsy (EUS-FNB) using the new “core” needles for acquiring pancreatic tissue. We aimed to investigate the usefulness of EUS-FNB for diagnosing AIP with one such needle, a 22-gauge Franseen needle.Methods Patients who met the imaging diagnostic criteria for AIP based on the International Consensus Diagnostic Criteria (ICDC) were enrolled in the study. All patients underwent EUS-FNB with a 22-gauge Franseen needle. Histological findings were evaluated based on the ICDC, and the detection rates of level 1 and level 1 or 2 histology were calculated.Results 56 patients from 11 different institutions were enrolled in the final analysis (55 suspected to have type 1 AIP and one with type 2 AIP). Lymphoplasmacytic infiltration, obliterative phlebitis, storiform fibrosis, and > 10 IgG4-positive cells per high-power field were detected in 55 (100 %), 24 (43.6 %), 40 (72.7 %), and 36 (65.5 %) of the 55 patients, respectively. The detection rates of level 1 and level 1 or 2 histology for AIP were 58.2 % (95 % confidence interval [CI] 44.1 % – 71.3 %) and 92.7 % (95 %CI 82.4 % – 98.0 %), respectively, which were apparently higher than our historical results (7.9 % [95 %CI 1.7 % – 21.4 %] and 62.2 % [95 %CI 46.5 % – 76.2 %], respectively) using a conventional needle.Conclusions EUS-FNB with a 22-gauge Franseen needle demonstrated favorable detection rates which would be clinically beneficial for the histological diagnosis of AIP.